2020
DOI: 10.3390/molecules25184249
|View full text |Cite
|
Sign up to set email alerts
|

The Physiochemical Properties and Adsorption Characteristics of Processed Pomelo Peel as a Carrier for Epigallocatechin-3-Gallate

Abstract: The NaOH-HCl- and ethanol-pretreated pomelo peel samples were prepared to apply to the batch adsorption for epigallocatechin-3-gallate (EGCG). The characteristics of peel samples were determined by Fourier transform infrared spectroscopy, scanning electron microscopy and a laser particle analyzer. The results of the physiochemical properties of the peel samples demonstrate that these peel samples have a promising adsorption capacity for EGCG, because of the increased potential binding sites on the surface comp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 52 publications
(83 reference statements)
0
2
0
Order By: Relevance
“…The BBP was grounded and sieved into powder with a standard mesh ring of 150-212 µ m. The BBP powder was submerged in 20 mL of 1 M HCl and sodium hydroxide (NaOH). The alkaline-acid treatment has demonstrated potential as a cost-effective method for modifying adsorbents, leading to their enhance efficiency for water treatment [30]. The BBP powder was mixed for 30 min with chemical activation solutions in an orbital shaker at 150 rpm.…”
Section: Banana Blossom Peels Adsorbent Preparationmentioning
confidence: 99%
“…The BBP was grounded and sieved into powder with a standard mesh ring of 150-212 µ m. The BBP powder was submerged in 20 mL of 1 M HCl and sodium hydroxide (NaOH). The alkaline-acid treatment has demonstrated potential as a cost-effective method for modifying adsorbents, leading to their enhance efficiency for water treatment [30]. The BBP powder was mixed for 30 min with chemical activation solutions in an orbital shaker at 150 rpm.…”
Section: Banana Blossom Peels Adsorbent Preparationmentioning
confidence: 99%
“…Moreover, based on the equation of ΔG ads 0 = −RT ln K L [44], where the values of R = 8.314 J K -1 mol -1 , T = 298.15 K, and K L = 7.46 × 10 4 L mol -1 , it has been found that the value of ΔG ads 0 is −27.8 kJ mol -1 . This result indicates that the adsorption of MO on Magnetite-CTAB-0.10 is dominated by both physisorption and chemisorption mechanisms (∆G ads 0 ranges from −20 to −80 kJ mol −1 [45][46]). It is predicted that the primary interaction in this adsorption is an electrostatic interaction between the positive surface charge on the adsorbent and the negative charge group on the adsorbate.…”
Section: Adsorption Isothermsmentioning
confidence: 99%